16. Integrated Collaborative Tools - Fujino, Lynn; Martindale, Neil; Mulder, Sharon; Woodward, Clare; Fahy, Patrick J. (International Review of Research in Open and Distributed Learning, 2002)
Previous reports in this series have featured examples of integrated products that combine into a single software package, techniques offered individually by other products. Increasing acceptance of online collaboration is generating interest in such tools on the part of product developers and users. The distance education (DE) market is now awash with integrated products involving methods ranging from the relatively standard text-based conferencing to synchronous and asynchronous audio and video conferencing techniques. Integrated products typically add a range of ancillary tools to these main features (e.g., whiteboards, polling methods, file sharing and email capability). When choosing an appropriate product for DE usage it is important to discern which of the multitude of features are essential in different situations. The current study examines five contrasting integrated products from the DE user’s perspective.